The crop mined phosphorus nutrition via modifying root traits and rhizosphere micro‐food web to meet the increased growth demand under elevated CO2 - Na Zhou; Xue Han; Ning Hu; Shuo Han; Meng Yuan; Zhongfang Li; Sujuan Wang; Yingchun Li; Hongbo Li; Zed Rengel; Yuji Jiang; Yilai Lou (iMeta)
Abstract Elevated CO2 (eCO2) stimulates productivity and nutrient demand of crops. Thus, comprehensively understanding the crop phosphorus (P) acquisition strategy is critical for sustaining agriculture to combat climate changes. Here, wheat (Triticum aestivum L) was planted in field in the eCO2 (550 µmol mol−1) and ambient CO2 (aCO2, 415 µmol mol−1) environments. We assessed the soil P fractions, root morphological and physiological traits and multitrophic microbiota [including arbuscular mycorrhizal fungi (AMF), alkaline phosphomonoesterase (ALP)‐producing bacteria, protozoa, and bacterivorous and fungivorous nematodes] in the rhizosphere and their trophic interactions at jointing stage of wheat. Compared with aCO2, significant 20.2% higher shoot biomass and 26.8% total P accumulation of wheat occurred under eCO2. The eCO2 promoted wheat root length and AMF hyphal biomass, and increased the concentration of organic acid anions and the ALP activity, which was accompanied by significant decreases in calcium‐bound inorganic P (Ca‐Pi) (by 16.7%) and moderately labile organic P (by 26.5%) and an increase in available P (by 14.4%) in the rhizosphere soil. The eCO2 also increased the growth of ALP‐producing bacteria, protozoa, and bacterivorous and fungivorous nematodes in the rhizosphere, governed their diversity and community composition. In addition, the eCO2 strengthened the trophic interactions of microbiota in rhizosphere; specifically, the eCO2 promoted the associations between protozoa and ALP‐producing bacteria, between protozoa and AMF, whereas decreased the associations between ALP‐producing bacteria and nematodes. Our findings highlighted the important role of root traits and multitrophic interactions among microbiota in modulating crop P‐acquisition strategies, which could advance our understanding about optimal P management in agriculture systems under global climate changes.